Arabidopsis Qc-SNARE genes BET11 and BET12 are required for fertility and pollen tube elongation - Bolaños Villegas, Pablo Alberto (2015)
ORCID IDs: 0000-0003-1729-0561 (P.B.-V.); 0000-0003-3459-1331 (G.-Y.J.)